Management of Montados and Dehesas for High Nature Value: an interdisciplinary pathway - Ferraz-de-Oliveira, M.I. (2016)
Mediterranean oak woodlands, Montados in Portugal and Dehesas in Spain have long been acknowledged as potential land use systems of high nature and social value providing relevant ecosystem services and biodiversity conservation. Nevertheless, these systems are now under severe threat, both due to abandonment in certain areas and overuse in others, extremes that may be limited by appropriate management practices and strategies. The High Nature Value concept can be a pathway for the understanding and assessment of management practices best adapted to the balance of the Montado and Dehesa, and also to the assessment of the thresholds of change, so that the long term sustainability of the Montado systems is preserved. This special issue aims to contribute for the understanding of how the Montado and Dehesa classification as High Nature Value may be a path for sustainable management. This classification can be achieved by different ways and implies different components of the Montado, and thus the first four papers of this special issue address different approaches and methodologies for the identification of HNV Dehesas and Montados, the following seven papers deal mostly with the effect of management practices on biodiversity and other Dehesas and Montados values and finally the last two papers address the causes for Montado decline and suggest mitigation measures for that decline.